Prosthetic ecologies: vulnerable bodies and the dismodern subject in Sir Gawain and the Green Knight. Issue 7 (9th November 2016) - Godden, Richard H.
ABSTRACT: This essay reads Sir Gawain and the Green Knight through the lens of Disability Studies. Specifically, it explores how the technologies of chivalry (a knight's armour, his shield, and even his reputation) serve as prostheses that aid in shaping and fashioning the chivalric subject. As prostheses, Gawain's objects simultaneously complete a body that is consistently exposed as vulnerable while also bringing attention to its incompleteness. Without these objects, however, there would be no figure named Gawain. This analysis of Gawain's chivalric accoutrement reveals him to be a dismodern subject, that is, as inhabiting a subject position marked by interdependency, where completion means existing in a network with other bodies, social and material. This essay also looks to the new materialism in order to understand how Gawain's objects can become things, exerting a thing-power that promises excess and uncanniness alongside completion and wholeness. By bringing together Disability Studies and the new materialism, we can move beyond binaries of whole/part, healthy/unhealthy, subject/object in order to consider how the self functions in a prosthetic ecology comprised of both the human and the nonhuman.